Pengaruh Terapi Musik Islami Terhadap Kecemasan Pada Penderita Hipertensi Di Desa Batu Belah Wilayah Kerja Puskesmas Air Tiris - Syafitri , Ramadiani; Safitri , Yenny; Dhilon , Dhini Anggraini (Evidence Midwifery Journal, 2023)
The increase in the incidence of hypertension in the community occurs because of worry or anxiety, tension in oneself, social status, and anxiety, especially feelings of anxiety that can worsen the condition of people with hypertension. One of the treatments to reduce anxiety in hypertension sufferers is non-pharmacological therapy, namely Islamic music therapy. The aim of the study was to determine the effect of Islamic music therapy on anxiety in hypertensive patients in Batu Belah Village, Air Tiris Public Health Center. The research design was pre-experimental with a one group pre test – post test design approach. The population in the study was 1,147 hypertension sufferers in Batu Belah Village and the number of samples in this study were 13 people. The sampling technique used was purposive sampling. Data collection tools are observation sheets and HARS questionnaires. The results of this study showed that the average anxiety before giving Islamic music therapy was 21.77 ± SD 2.204 and included in the moderate anxiety category, while the average anxiety after giving Islamic music therapy was 14.46 ± SD 2.787 and included in the mild anxiety category. After conducting the Paired T-test, P value = 0.000 (p?0.05) means that there is an effect of Islamic music therapy on anxiety in hypertension sufferers in Batu Belah Village, Air Tiris Public Health Center. The results of this study are expected to be useful for hypertension sufferers and to add new knowledge insights for health workers and nursing students in improving nursing knowledge, as well as a source of references and reading related to the provision of Islamic music therapy as an alternative treatment for hypertension sufferers.